Steamed Red Bean Flour Sponge Cake with Date Substitution: A Healthy Snack to Prevent Anemia in Adolescent Girls - Radella; Dewi Woro; Hidayatusy Syukrina Puteri; Asep Jalaludin; Ajib Jayadi; Nurhartanto (CV. CENDIKIA JENIUS INDONESIA, 2025)
Adolescent girls are vulnerable to anemia due to increased iron requirements during growth. If untreated, this condition may impair concentration, immunity, and productivity. This study aimed to develop a healthy snack in the form of steamed sponge cake made from red bean flour with date substitution to prevent anemia in adolescent girls. This experimental study used a Completely Randomized Design (CRD) with five formulations and involved 25 female adolescents aged 12–14 as panelists. Data were collected through organoleptic testing and nutritional analysis using ANOVA and One-Sample T-Test. Results showed that formulation F2 (120 g wheat flour, 45 g red bean flour, 30 g dates) was most preferred and contained 6.7 mg of iron per 100 g. Consuming 100 g of F2 cake could fulfill 89.3% of the daily iron requirement. Conclusion: Red bean flour steamed cake with dates has the potential to be a nutritious and acceptable functional snack for adolescent girls. Further research is recommended to replicate nutrient analysis and consider large-scale production as a nutritional intervention for anemia prevention.